Pendekatan Perencanaan Perkotaan Dalam Konteks Kesehatan Perkotaan - Ratodi, Muhamad (EMARA Indonesian Journal of Architecture, 2016)
Urban planning potentially has a close relationship with the the study of urban health. But the relationship between these two major relatively new concern for urban planners and urban health experts. During the 19th century, the relationship between the city as a subject of planning, urban design, governance and health problems such as infectious diseases, malnutrition, housing conditions and workplace as well as the mental health is seen clearly. The attention currently focused to the urban planning that emphasized on urban health as well as the urban health that focus on the wellbeing of the urban population. In this article will describe primaries approaches and strategies of urban planning againts urban problems that highlight the main conceptual ideas which are relevant to urban health